Noveon AA1 as enhancer of HPMC as a direct compression matrix for controlled release - Sara Laguna-López, Leopoldo Villafuerte-Robles (Journal of Applied Pharmaceutical Science, 2014)
This work aimed the assessment of the effect of different proportions of Noveon AA1 on performance of HPMC as a controlled release agent for direct compression tablets. The functionality of polymer blends was determined using dissolution profiles, compactibility profiles and the powders compressibility index. Ten percent HPMC allows a metronidazole release after 3 h of 85%, an exponent n=0.48 and a release constant K=6.9. The increasing polymer substitution by Noveon AA1 decreases drug dissolution up to 36%, increases the exponent to 1.0 and decreases the release constant to 0.2%. The metronidazole/HPMC blend shows a slower increasing and a lower potential of tablets compactibility (20 N) while its increasing substitution by Noveon AA1 attains faster increasing and higher potential compactibilities (39 N). The metronidazole/HPMC (90:10) blend shows a low compressibility index (14%) that increases up to 33.2% with increasing Noveon AA1 proportions. Noveon AA1 proportions ≤ 5% display good/passable powder flowabilities. Noveon AA1 enhances the overall controlled release performance of HPMC, inducing zero order release patterns without lag or burst effects and reducing drug release more efficiently. Noveon AA1 also improves the compactibility of metronidazole/HPMC blends, however, decreases their flowability; flowability is acceptable only at lesser polymer proportions.
Keywords: Tablet hardness, Compactibility, Powder flowability, compressibility index, Dissolution profile, Dissolution mechanisms, Metronidazole.